Faktor keberhasilan rehabilitasi dan rekonstruksi pascagempa berbasis persepsi lokal (Kasus: Kalurahan Segoroyoso, Kabupaten Bantul - Vicky Dwi Settyawan; Nur Miladan; Mochamad Primasakti Satyagraha (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2026)
The 2006 earthquake in Bantul Regency caused severe physical and socio-economic damage, necessitating extensive post-disaster rehabilitation and reconstruction. Segoroyoso Village, located along the Opak Fault, experienced one of the highest levels of damage yet demonstrated relatively successful and sustainable post-disaster recovery. This study aims to identify key factors influencing the success of post-earthquake rehabilitation and reconstruction based on local community perceptions in Segoroyoso Village, Bantul Regency. A quantitative approach using Exploratory Factor Analysis (EFA) was employed to analyze questionnaires administered to 97 respondents. A total of 24 variables representing social, economic, institutional, and physical aspects were analyzed using JASP software. The results identify four main factors influencing post-disaster recovery success: (1) information management and coordination, (2) level of physical damage caused by the earthquake, (3) regional and community economic recovery, and (4) community participation and collaboration. The findings indicate that successful post-disaster recovery is determined not only by technical support and external assistance but also by strong community involvement, institutional readiness, and effective cross-sectoral information and coordination systems. This study contributes to the formulation of adaptive and participatory post-disaster regional development strategies based on local data.